HOLOCAUSTO BRASILEIRO - De Carli, Eliane Maria; Alban, Gabriela; Sartori, Suelen; Braitenbach, Roberta (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2019)